2018
DOI: 10.3390/rel9080246
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatisation and Ritual: An Analysis of the Stigmatisation of Pentecostalism in Chile

Abstract: Pentecostalism has been one of the most successful religious movements in Chile due to both its historical growth and its ascendancy in different spheres of society. Nevertheless, from its origins to the present day, it has also been the most stigmatised religious movement in the country. Studies have explained this phenomenon by referring to variables of social class or religious rivalry. However, they have forgotten a factor that is key to this problem and to Pentecostalism: its ritual dimension. The aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Pentecostalism was from the very beginning the poor man´s religion, a fact that can take us some way in understanding its lack of respectability in Chilean society. However, important historical research has suggested that the stigmatization of Pentecostalism was mainly related to its noisy and emotional forms of worship and the spiritual manifestations such as glossolalia, all of which outsiders saw as evidence of irrational and sectarian fanaticism (Mansilla 2007;Munoz and Fernández-Mostaza 2018). Methodist authorities in Chile discredited the spiritual manifestations of Pentecostalism, and early press coverage of the Pentecostal revival was anything but sympathetic, with one newspaper article describing the revival as the work of a madman (Munoz and Fernández-Mostaza 2018, 7-8).…”
Section: Stigma and Confrontationmentioning
confidence: 99%
See 2 more Smart Citations
“…Pentecostalism was from the very beginning the poor man´s religion, a fact that can take us some way in understanding its lack of respectability in Chilean society. However, important historical research has suggested that the stigmatization of Pentecostalism was mainly related to its noisy and emotional forms of worship and the spiritual manifestations such as glossolalia, all of which outsiders saw as evidence of irrational and sectarian fanaticism (Mansilla 2007;Munoz and Fernández-Mostaza 2018). Methodist authorities in Chile discredited the spiritual manifestations of Pentecostalism, and early press coverage of the Pentecostal revival was anything but sympathetic, with one newspaper article describing the revival as the work of a madman (Munoz and Fernández-Mostaza 2018, 7-8).…”
Section: Stigma and Confrontationmentioning
confidence: 99%
“…Despite their emphasis on the need to be separated from the 'world,' Pentecostals also insist on confronting and reaching out for it by preaching, usually in small groups, on streets and in public squares. In the early stages of the Pentecostal movement, many viewed this type of evangelism as a provocation and an attack on public order (Munoz and Fernández-Mostaza 2018). Nowadays, non-Pentecostal Chileans are accustomed to Pentecostal street preachers as a standard and hardly significant part of public life.…”
Section: Stigma and Confrontationmentioning
confidence: 99%
See 1 more Smart Citation
“…(iii) The Emotivity of the Expression of the Neoliberal Religiosities An additional element that, according to Latin American sociologists of religion, makes Pentecostal communities different, especially compared to both traditional strands of Catholic doctrine (including Liberation Theology) and historical Protestantism, is the offering of a deeply emotive religious experience accessible to all believers, which is manifested in a whole series of rituals that constitute "the hallmark of Pentecostalism" (Robbins 2009). These rituals, moreover, are often the main target of mockery and stigmatization by outside observers and members of other religions (Muñoz and Fernández-Mostaza 2018).…”
Section: (I) Prosperity Gospel As the Theology Of The New And Successful Contemporary Religious Manifestationsmentioning
confidence: 99%
“…For my arguments I will rely, in particular, on the following texts: Marzal (2002), Chestnut (2003), Espinosa (2004), Algranti (2007), Bergunder (2009), Parker (2013), Beltrán (2013), Lindhardt (2016), Freston (2016), Morello et al (2017), Somma et al (2017), Baptista andOspina (2017), pp. 11-106 in Guadalupe andGrundberger (2018), Moreira (2018), Muñoz and Fernández-Mostaza (2018), Semán (2019), andFrigerio (2019), as well as in the study conducted by the Pew Research Center (2014). Among all these, I will highlight the study by Beltrán (2013) for its systematicity, its deep empirical component, and the detailed description of its sources and objects of study.…”
mentioning
confidence: 99%